Kinematic sequencing of the short game swing in male collegiate golfers - Walsh, M. S.; McGuire, T.; Piccard, C.; Kwon, Y.-H.; Smith, D. L. (ISBS Proceedings Archive: Vol. 42: Iss. 1, 2024)
Approach shots are crucial to the success of elite golfers. The primary purpose of this study was to compare kinematics of golf shots at four target distances (30, 50, and 70 yards, and full swing) in collegiate, male golfers. Participants were instructed to hit five successful shots at each target distance. A motion capture system recorded kinematic and temporal parameters of the golfers and a golf simulator collected ball carry distance of each shot. Distance had a significant (p = 0.05) effect on swing phase timing, angular velocities, and motion sequencing. Movement sequencing within the short game displayed irregular patterns across all distances and phases. The findings of this study show that the short game swing did present its own unique motion patterns that will require practice as its own skill.